2017
DOI: 10.1183/13993003.02096-2016
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and risk factors associated with spirometric restriction

Abstract: The restrictive spirometric pattern is associated with a substantial morbidity and mortality burden. We sought to determine to what extent spirometric restriction is associated with impaired quality of life.We used data from two large population-based European cohorts: 6698 European Community Respiratory Health Survey (ECRHS) and 6069 Swiss Cohort Study on Air Pollution and Lung and Heart Diseases in Adults (SAPALDIA) adult participants. The restrictive pattern was defined as forced expiratory volume in 1 s (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 31 publications
3
53
0
1
Order By: Relevance
“…physical activity, such as exercise performance and the physical component of quality of life, are reduced in subjects with a restrictive spirometry pattern [9,14], which supports the plausibility of our results.…”
Section: Main Findingssupporting
confidence: 86%
See 3 more Smart Citations
“…physical activity, such as exercise performance and the physical component of quality of life, are reduced in subjects with a restrictive spirometry pattern [9,14], which supports the plausibility of our results.…”
Section: Main Findingssupporting
confidence: 86%
“…Second, interventions encouraging physical activity in individuals with a restrictive spirometry pattern should be designed and tested. Having a restrictive spirometry pattern is associated with poor quality of life and functional limitation [9,10], therefore it is plausible that increasing one's physical activity could improve quality of life and stabilise decreases in lung capacity. Finally, our results suggest that physical inactivity may be behind the previously observed poor prognosis of restrictive spirometry pattern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study in a large Danish cohort, ÇOLAK et al [14] found that even when FEV 1 /FVC >0.8, the presence of chronic respiratory symptoms is associated with respiratory-related hospitalisation and death. Remarkably, PRISm patients with such restrictive spirometric pattern seem to have a lower quality of life even when they are asymptomatic [15].…”
mentioning
confidence: 95%